Effects of floating-leaved macrophytes on water quality and phytoplankton: an in situ experiment in a Chinese shallow lake. Issue 57 (7th December 2016) - Ji, Gaohua; Xu, Zu-Xin; Wang, Li-Qing
Abstract: In this study, in situ experiments were conducted to evaluate the effects of floating-leaved macrophytes (FLMs, i.e. Trapa uncinata and Nymphaea tetragona ) on water quality and algal growth and to investigate the potential inhibition of phytoplankton growth by FLMs. Enclosures were established in a shallow subtropical eutrophic lake, and FLMs were planted therein. Open water areas in the enclosure with FLMs, an enclosure without FLMs, and the lake water surrounding the enclosures served as the control groups. Physical parameters, nutrient contents, and algae were evaluated for six sampling sites at 10-d intervals. Treatment with FLMs significantly promoted water transparency and reduced turbidity. However, the concentrations of nutrients were similar in the different sites, despite the nutrient absorption by FLMs. The overall algal abundance was reduced in the presence of FLMs, and this was shown in chlorophyll-a, algal density, and biomass. FLM treatments promoted changes in the algal community composition, benefitting metaphytic species adapted to higher transparency. A principal components analysis showed that algal attributes were higher in the control areas than in the FLM-covered areas, despite the similar nutrient concentrations. This indicated that the inhibition of algae in this study was based not on nutrient competition but instead on the shading effect. Using FLMs as a management tool to create a clear water state may be one solution for turbid waters in subtropical eutrophic shallow lakes.